El gasto promedio y la condición de pobreza de las personas en el Perú periodo 2019-2023 - Panduro Vela, Abel Alexander (2025)
The National Institute of Statistics and Informatics (INEI) measures the well being of the population through their spending, as it is a more accurate indicator than average income, since a consumer can allocate part of their income to savings despite having unmet basic needs. The research seeks to determine the type of association between poor people and the average monthly spending made during the five-year period 2019 - 2023. For this purpose, this Quantitative - Correlational research was carried out, with a Non-experimental design. It was concluded that the average spending carried out each month by the population is inversely related to the number of poor people in Peru, evaluated in the period 2019 - 2023, since the value of the Correlation Coefficient was r = -0.929730636 and the Coefficient of Determination was R2 = 0.864399055. The distribution of average expenditure is mainly concentrated on the purchase of food consumed within the home, with S/. 269.00 being allocated to this item, representing 31.18% of the total. Metropolitan Lima and El Callao are the geographic area where residents spend the most monthly, reaching S/. 1,005.00; a figure that exceeds the national average of S/. 878.00. The greatest poverty was found in the rural highlands, affecting 45.42% of the population in this area.